Remote (250 km) Fiber Bragg Grating Multiplexing System - Manuel Lopez-Amo; Montserrat Fernandez-Vallejo; Sergio Rota-Rodrigo (Sensors, 2011)
We propose and demonstrate two ultra-long range fiber Bragg grating (FBG) sensor interrogation systems. In the first approach four FBGs are located 200 km from the monitoring station and a signal to noise ratio of 20 dB is obtained. The second improved version is able to detect the four multiplexed FBGs placed 250 km away, offering a signal to noise ratio of 6–8 dB. Consequently, this last system represents the longest range FBG sensor system reported so far that includes fiber sensor multiplexing capability. Both simple systems are based on a wavelength swept laser to scan the reflection spectra of the FBGs, and they are composed by two identical-lengths optical paths: the first one intended to launch the amplified laser signal by means of Raman amplification and the other one is employed to guide the reflection signal to the reception system.